2008
DOI: 10.2340/16501977-0139
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting in intensive care patients: Ultrasound observation of the M. quadriceps femoris muscle layer

Abstract: Loss of muscle mass shows a negative correlation with length of stay, and seems to be higher during the first 2-3 weeks of immobilization/intensive care unit stay. Ultrasound is a valid and practical measurement tool for documenting muscle mass (e.g. muscle layer thickness) as part of the daily routine at an intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
263
5
22

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(310 citation statements)
references
References 29 publications
8
263
5
22
Order By: Relevance
“…We demonstrated that a previously developed four‐site protocol14 provided stronger correlations with lean tissue mass when using minimal compression ( R 2  = 0.82), compared with maximal compression ( R 2  = 0.66), at the same site‐specific landmarks using DXA. While the four‐site protocol is strongly associated with appendicular lean tissue mass ( R 2  = 0.72), we observed wide limits of agreement (−5.67, 5.67 kg).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We demonstrated that a previously developed four‐site protocol14 provided stronger correlations with lean tissue mass when using minimal compression ( R 2  = 0.82), compared with maximal compression ( R 2  = 0.66), at the same site‐specific landmarks using DXA. While the four‐site protocol is strongly associated with appendicular lean tissue mass ( R 2  = 0.72), we observed wide limits of agreement (−5.67, 5.67 kg).…”
Section: Discussionmentioning
confidence: 88%
“…Participants underwent anthropometric measures, a whole‐body DXA scan and ultrasound assessments, in a supine or prone position, using the previously established nine‐site 12 and four‐site 14 protocols. A subset ( n  = 16) of participants had inter‐rater reliability performed by using the four‐site protocol for a single leg (alternating between dominant and non‐dominant legs).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…This negative effect on muscle mass has been reported previously [31,34]. Adequate muscle strength in the lower limbs, primarily in the abductor muscle, is required for satisfactory rehabilitation [35].…”
Section: Discussionmentioning
confidence: 94%
“…However, large improvements in GFR from baseline after critical illness would seem implausible, whereas large and sustained falls in creatinine generation have been shown in animal models of sepsis (14), patients with advanced CKD (15), and critically ill humans (16)(17)(18), with greatest decrease occurring in the sickest patients (16). Skeletal muscle is the major source of creatinine production, and critical illness is associated with profound loss of skeletal muscle protein (10,19,20), with muscle thickness steadily decreasing over time after ICU admission (10,21,22). Loss of muscle mass can persist long after hospital discharge (23).…”
Section: Study Findingsmentioning
confidence: 99%